2012
DOI: 10.17221/6465-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of milk leukocytes in response to intramammary infusion of amoxicillin plus sulbactam during bovine subclinical mastitis

Abstract: ABSTRACT:The therapeutic potential of amoxicillin plus sulbactam and its effect on dynamics of milk leukocytes in bovine sub clinical mastitis were investigated in this study. Therapeutic efficacy was measured by somatic cell count and total bacterial count of the milk, whereas, the dynamics of milk leukocytes were assessed by measuring phagocytosis, hydrogen peroxide production, myeloperoxidase and lactoperoxidase enzyme levels in the milk leukocytes. Forty-five crossbred cows were randomly divided into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Because amoxicillin has the same pharmacokinetic features as those of parenteral penicillin G, a better efficacy for treating mastitis through the intramuscular route is anticipated [14]. Moreover, amoxicillin, alone or in combination with β-lactamase inhibitors, has been widely used to treat clinical mastitis in dairy cows [15,16]. According to Roberson et al [15], IMM amoxicillin appeared to be an effective treatment for environmental streptococci in cases of mild or moderate clinical mastitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because amoxicillin has the same pharmacokinetic features as those of parenteral penicillin G, a better efficacy for treating mastitis through the intramuscular route is anticipated [14]. Moreover, amoxicillin, alone or in combination with β-lactamase inhibitors, has been widely used to treat clinical mastitis in dairy cows [15,16]. According to Roberson et al [15], IMM amoxicillin appeared to be an effective treatment for environmental streptococci in cases of mild or moderate clinical mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…According to Roberson et al [15], IMM amoxicillin appeared to be an effective treatment for environmental streptococci in cases of mild or moderate clinical mastitis. De and Mukherjee [16] reported a substantial reduction in SCC and total bacterial count in cows that were provided IMM administrations of 300 mg of amoxicillin + sulbactam during the posttreatment period. Similarly, another study reported a successful clinical recovery of bovine mastitis in lactating cows treated with a combination of amoxicillin and clavulanic acid by IMM infusion [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that AMX alone or in combination with β-lactamase inhibitors is potentially useful for the treatment of mastitis caused by pathogenic organisms (Roberson et al 2004;Sharma et al 2010). A very effective clinical recovery of bovine mastitis was reported in lactating cows treated with intramammary infusion of AMX plus SUL (DeOliveira et al 2000;Sharma et al 2010;De and Mukherjee 2012). Synulox ® LC, a combination drug comprising AMX (200 mg), clavulanic acid (CLAV, 50 mg), and PSL (10 mg) in a 3 g syringe, was developed by Pfizer Pharmaceuticals Inc. (New York, NY, USA.)…”
mentioning
confidence: 99%
“…It has been observed that AMX alone or in combination with β-lactamase inhibitors is potentially useful for the treatment of mastitis caused by pathogenic organisms [19,21]. A very effective clinical recovery of bovine mastitis was reported by lactating cows treated with intramammary infusion of AMX plus SUL [10][11]21]. Synulox ® LC, a combination drug that comprising AMX (200 mg), clavulanic acid (CLAV, 50 mg) and PSL (10 mg) in a 3 g syringe, was developed by Pfizer Pharmaceutical Inc. (New York, NY, U.S.A.) and used for the treatment of bovine mastitis.…”
mentioning
confidence: 99%